Targeting Protein Kinases Degradation by PROTACs - Yu, Fei; Cai, Ming; Shao, Liang; Zhang, Jihong (Frontiers in Chemistry, 2021)
Kinase dysregulation is greatly associated with cell proliferation, migration and survival, indicating the importance of kinases as therapeutic targets for anticancer drug development. However, traditional kinase inhibitors binding to catalytic or allosteric sites are associated with significant challenges. The emergence of resistance and targeting difficult-to-degrade and multi-domain proteins are significant limiting factors affecting the efficacy of targeted anticancer drugs. The next-generation treatment approaches seem to have overcome these concerns, and the use of proteolysis targeting chimera (PROTAC) technology is one such method. PROTACs bind to proteins of interest and recruit E3 ligase for degrading the whole target protein via the ubiquitin-proteasome pathway. This review provides a detailed summary of the most recent signs of progress in PROTACs targeting different kinases, primarily focusing on new chemical entities in medicinal chemistry.